Non-abelian teleparallelism as an extended gauge theory: A geometrical view - Barbosa, Ana Lucia [UNESP]; de Andrade, V. C. (World Scientific Publishing, 2006)
Analyzing the geometry of a non-Abelian Teleparallel Theory and the one of an Extended Gauge Theory and comparing one to the other, we find some similar structures that may help us to understand the gravitational model emerging from each theory.